Comparative Analysis of Idiomatic Expressions in English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is devoted to a comparative analysis of idiomatic expressions in English and Uzbek languages, highlighting their semantic, cultural, and structural features. Idioms are an integral part of any language, as they reflect the worldview, traditions, values, and way of thinking of a particular nation. The study emphasizes that idiomatic expressions not only enrich the vocabulary of a language but also serve as a mirror of national mentality, enabling speakers to convey deep meanings, emotions, and attitudes through figurative speech. By examining English and Uzbek idioms side by side, the research reveals both similarities and differences that arise due to historical development, cultural heritage, and socio-linguistic factors. The article explores the classification of idioms according to their meaning, origin, and usage in both languages. Particular attention is paid to idioms related to nature, animals, everyday life, and social behavior, since these categories are widely used in daily communication. Comparative examples demonstrate how idiomatic equivalents may exist across the two languages, but with certain semantic shifts, cultural adaptations, or even complete absence of correspondence. For instance, some idioms in English have direct analogues in Uzbek, while others require descriptive translation to preserve their pragmatic and expressive functions. The paper also discusses the challenges faced by translators and language learners in understanding and using idiomatic expressions correctly. Since idioms are often metaphorical and context-dependent, their meaning cannot always be derived from individual word components. Therefore, a cultural-linguistic approach is necessary for effective comprehension and translation. The analysis underlines the importance of idioms in language teaching, intercultural communication, and translation studies, as they provide valuable insights into the cultural identity of nations. In conclusion, the comparative study of English and Uzbek idiomatic expressions demonstrates that despite differences in linguistic systems, idioms in both languages share a common purpose — to enrich communication, create vivid imagery, and convey national and cultural experience. The findings contribute to a deeper understanding of cross-linguistic similarities and divergences, and they can be applied in linguistics, translation practice, and foreign language teaching.